Pentingnya Strategi Pembelajaran Efektif Yang Berpusat Pada Siswa Sekolah Dasar - Izzatunnisa Izzatunnisa; Amini Amini; Chalijah Adha; Saidatul Fadilla Nasution; Muhammad Fathoni (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Effective learning is essential to achieve educational goals. In the context of learning, the challenge involves students' lack of understanding due to a focus on memorization without deep comprehension. Teachers play a crucial role in addressing this issue by implementing teaching strategies that encourage understanding and application of knowledge. This research employs a qualitative approach to explore the understanding of effective teaching strategies with a focus on the central role of students. The findings suggest that effective learning requires the teacher's role in designing engaging, student-focused lessons. The quality of learning is measured through aspects such as student health, supportive environments, appropriate program content, student-centered learning processes, and holistic learning outcomes. Well-implemented teaching strategies create positive impacts, including organized classrooms, optimal resource utilization, and increased student motivation.